Higher education attainment: the case of intergenerational transmission of education in Portugal - Pedro Telhado Pereira (Institute for the Study of Labor (IZA), 2010)
The lack of formal education and competences of the Portuguese workers is one of the biggest problems of the country. This lack is disappearing as quickly as desired and the young generations still lag far behind those in other OECD countries. This paper studies the intergenerational transmission of education achievement, in particular higher education completion, seeking to determine the influence on future attainment of parents' education and labor market conditions while the child was growing up. We conclude that the education of the parents is very important, even if it is only one of them that has it. This influence seems not to be independent of the gender of the parent who has it. The fact that the parents face unemployment has a negative effect on the educational achievement of the child. Females generally perform better than males, but there are exceptions. For instance, it is significantly lower if the father has low education and the mother has secondary or higher education.
Keywords: I21; I28; J11; 330; Demand for schooling; human capital; parent's education; Bildungsverhalten; Generationenbeziehungen; Bildungsniveau; Familiensoziologie; Portugal